Facile strategy for synthesis of ,-heterobifunctionalized poly (epsilon-caprolactones) and poly (methyl methacrylate)s containing ``clickable'' aldehyde and allyloxy functional groups using initiator approach - Sane, Prakash S.; Tawade, Bhausaheb V.; Parmar, Indravadan; Kumari, Savita; Nagane, Samadhan; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
Two new initiators, namely, 4-(4-(2-(4-(allyloxy) phenyl)-5-hydroxypentane 2-yl) phenoxy)benzaldehyde and 4-(4-(allyloxy) phenyl)-4-(4-(4-formylphenoxy) phenyl) pentyl 2-bromo-2-methyl propanoate containing clickable hetero-functionalities namely aldehyde and allyloxy were synthesized starting from commercially available 4,4-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of epsilon-caprolactone and atom transfer radical polymerization of methyl methacrylate. Well-defined -aldehyde, -allyloxy heterobifunctionalized poly(epsilon-caprolactones) (Mn,GPC: 590029,000, PDI: 1.261.43) and poly(methyl methacrylate)s (Mn,GPC: 530028800, PDI: 1.191.25) were synthesized. The kinetic study of methyl methacrylate polymerization demonstrated controlled polymerization behavior. The presence of aldehyde and allyloxy functionality on polymers was confirmed by 1H NMR spectroscopy. Aldehyde-aminooxy and thiol-ene metal-free double click strategy was used to demonstrate reactivity of functional groups on polymers. (c) 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013, 51, 2091-2103
Keywords: atom transfer radical polymerization; Click chemistry; functional polymers; ring opening polymerization

New atom transfer radical polymerization initiator based on phenolphthalein for the synthesis of bis-allyloxy functionalized polystyrene macromonomers - Patil, Sachin S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Polymer International, 2015)
A new atom transfer radical polymerization (ATRP) initiator, namely 2-(1,1-bis(4-(allyloxy)phenyl)-3-oxoisoindolin-2-yl)ethyl 2-bromo-2-methylpropanoate, was synthesized starting from phenolphthalein, a commercially available and an inexpensive chemical. Well- defined bis-allyloxy functionalized polystyrene macromonomers (M-n,M-GPC 4800-11 700gmol(-1)) with controlled molecular weight and narrow molecular weight distribution (1.05-1.09) were synthesized using ATRP by varying the monomer to initiator feed ratio. The presence of allyloxy functionality on polystyrene was confirmed by Fourier transform infrared and H-1 NMR spectroscopy. A kinetic study of polymerization revealed pseudo-first-order kinetics with respect to monomer consumption. Initiator efficiency was found to be in the range 0.80-0.95. Matrix-assisted laser desorption ionization time of flight spectra showed a narrow molecular weight distribution with control over the molecular weight. The reactivity of the allyloxy groups on polystyrene was successfully demonstrated by quantitative photochemical thiol-ene click reaction with benzyl mercaptan as the model thiol reagent. Furthermore, the thiol-ene click reaction was exploited to introduce other reactive functional groups such as hydroxyl and carboxyl by reaction of ,-bis-allyloxy functionalized polystyrene with 2-mercaptoethanol and 3-mercaptopropionic acid, respectively. (c) 2014 Society of Chemical Industry
Keywords: atom transfer radical polymerization; bis-allyloxy functionalized polystyrene; functional initiator; phenolphthalein; thiol-ene click reaction

Convenient synthesis of alpha,alpha `- homo- and alpha,alpha `-hetero-bifunctionalized poly(epsilon-caprolactone)s by ring opening polymerization: the potentially valuable precursors for miktoarm star copolymers - Patil, Sachin S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Two new ring opening polymerization (ROP) initiators, namely, (3-allyl-2-(allyloxy)phenyl)methanol and (3-allyl-2-(prop-2-yn-1-yloxy)phenyl)methanol each containing two reactive functionalities viz. allyl, allyloxy and allyl, propargyloxy, respectively, were synthesized from 3-allylsalicyaldehyde as a starting material. Well defined -allyl, -allyloxy and -allyl, -propargyloxy bifunctionalized poly(epsilon-caprolactone)s with molecular weights in the range 4200-9500 and 3600-10,900 g/mol and molecular weight distributions in the range 1.16-1.18 and 1.15-1.16, respectively, were synthesized by ROP of epsilon-caprolactone employing these initiators. The presence of -allyl, -allyloxy and -allyl, -propargyloxy functionalities on poly(epsilon-caprolactone)s was confirmed by FT-IR, H-1, C-13 NMR spectroscopy, and MALDI-TOF analysis. The kinetic study of ROP of epsilon-caprolactone with both the initiators revealed the pseudo first order kinetics with respect to epsilon-caprolactone consumption and controlled behavior of polymerization reactions. The usefulness of -allyl, -allyloxy functionalities on poly(epsilon-caprolactone) was demonstrated by performing the thiol-ene reaction with poly(ethylene glycol) thiol to obtain (mPEG)(2)-PCL miktoarm star copolymer. -Allyl, -propargyloxy functionalities on poly(epsilon-caprolactone) were utilized in orthogonal reactions i.e copper catalyzed alkyne-azide click (CuAAC) with azido functionalized poly(N-isopropylacrylamide) followed by thiol-ene reaction with poly(ethylene glycol) thiol to synthesize PCL-PNIPAAm-mPEG miktoarm star terpolymer. The preliminary characterization of A(2)B and ABC miktoarm star copolymers was carried out by H-1 NMR spectroscopy and gel permeation chromatography (GPC). (c) 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 844-860
Keywords: 3-allylsalicyaldehyde; alpha `-allyloxy and alpha-allyl; alpha `-propargyloxy bifunctionalized poly (epsilon-caprolactone)s; alpha-allyl; atom transfer radical polymerization; orthogonal reactions; ring-opening polymerization; star copolymers